The binding energy and dynamics of charge-transfer states in organic photovoltaics with low driving force for charge separation - Dong,Y; Cha,H; Zhang,J; Pastor,E; Tuladhar,PS; McCulloch,I; Durrant,JR; Bakulin,AA (Journal of Chemical Physics, 2019)
Recent progress in organic photovoltaics (OPVs) has been enabled by optimization of the energetic driving force for charge separation, and thus maximization of open-circuit voltage, using non-fullerene acceptor (NFA) materials. In spite of this, the carrier dynamics and relative energies of the key states controlling the photophysics of these systems are still under debate. Herein, we report an in-depth ultrafast spectroscopic study of a representative OPV system based on a polymer donor PffBT4T-2OD and a small-molecule NFA EH-IDTBR. Global analysis of the transient absorption data reveals efficient energy transfer between donor and acceptor molecules. The extracted kinetics suggest that slow (∼15 ps) generation of charge carriers is followed by significant geminate recombination. This contrasts with the "reference" PffBT4T-2OD:PC71BM system where bimolecular recombination dominates. Using temperature-dependent pump-push-photocurrent spectroscopy, we estimate the activation energy for the dissociation of bound charge-transfer states in PffBT4T-2OD:EH-IDTBR to be 100 ± 6 meV. We also observe an additional activation energy of 14 ± 7 meV, which we assign to the de-trapping of mobile carriers. This work provides a comprehensive picture of photophysics in a system representing new generation of OPV blends with a small driving force for charge separation.